Metal organic frameworks (MOFs) with therapeutic and biomedical applications: a patent review. (3rd October 2021) - Teixeira de Alencar Filho, José Marcos; Sampaio, Pedrita Alves; Silva de Carvalho, Iure; Rocha da Silva, Ademar; Pereira, Emanuella Chiara Valença; Araujo e Amariz, Isabela; Nishimura, Rodolfo Hideki Vicente; Cavalcante da Cruz Araújo, Edigênia; Rolim-Neto, Pedro José; Rolim, Larissa Araújo
ABSTRACT: Introduction : Metal organic frameworks (MOFs) are a recent group of nano porous materials with exceptional physical properties, such as large surface areas, high pore volumes, low densities and well-defined pores. This type of material has been used frequently for biomedical and therapeutic applications, such as drug delivery systems and theranostic materials. Areas covered : In this review, the authors searched for patents filed in the last 10 years, found in different databases, related to the therapeutic or biomedical application of MOFs for use in different health fields. The possibility of these new materials becoming new therapeutic possibilities available to the population was emphasized. Expert opinion : The advances in research with MOFs have grown in the last 10 years and with that many possibilities for their applications have emerged in several areas, especially biomedical. The possibility of using these materials in drug delivery systems is the most common form of possibility of use in the health area, mainly due to easy obtaining and high reproducibility, which are seen very positively by the drug development technology sector.